Questionnaire of exposure to workplace sex-based harassment - Marcin Drabek (Nofer Institute of Occupational Medicine, 2020)
Background Polish research on gender-based sexual harassment at the workplace is relatively rare. The presented work aimed at developing a reliable tool to measure this phenomenon. Material and Methods The analyses of the psychometric properties of the Questionnaire of Exposure to Workplace Sex-Based Harassmen t were carried out on the basis of questionnaire data from employees of different occupational groups (N = 333). Results On the basis of exploratory and confirmatory factor analysis, 5 questionnaire scales were distinguished (5 types of behavior indicating sexual harassment): Sexual coercion , Unwanted sexual interest , Gender membership harassment , Harassment for deviating from gender role and Offensive comments on the employee or his/her private lif e. Cronbach's α indicator of internal consistency for the whole questionnaire equaled 0.93; and for particular scales it ranged 0.85-0.90. Conclusions The results of the performed analysis show that the Questionnaire of Exposure to Workplace Sex-Based Harassment has satisfactory psychometric characteristic. Med Pr. 2020;71(6):699-713